THE STRATEGY OF MEANING NEGOTIATION IN PRAGMATIC CLASS - Maarif, Amin Samsul (Universitas Galuh, 2020)
ABSTRACTThis article deals with the analysis of how the strategy of meaning negotiation engage in students’ interaction in pragmatic class, In conducting this study the writers used qualitative research in which descriptive study as the method of the study. Moreover, observation and interview were the instruments used in collecting the data. Based on the results, It was concluded that the meaning negotiation engage the students’ interaction in pragmatic classroom. The students engage emotionally, behaviourally, and cognitively. In addition, the interaction occured between teacher-students and students-students. Furthermore, some problems encountered by the teacher in implementing meaning negotiation strategy in pragmatic class were students’ understanding in comprehending the vocabulary, idiom, and meaning. It means that the teacher used to translate the material of English pragmatic material into Indonesian language. Morever, ther writers suggest to further researchers to investigate kinds of students engagement occured in English teaching learning process.Keywords: Second Language Acquisition, meaning negotiation, classroom interaction, students’ engagementABSTRAKArtikel ini membahas tentang bagaimana strategi negosiasi makna terlibat dalam interaksi siswa di kelas pragmatis. Dalam melakukan penelitian ini penulis menggunakan penelitian kualitatif dimana metode penelitiannya adalah studi deskriptif. Selain itu observasi dan wawancara merupakan instrumen yang digunakan untuk mengumpulkan data. Berdasarkan hasil penelitian dapat disimpulkan bahwa makna negosiasi melibatkan interaksi siswa dalam kelas pragmatis. Para siswa terlibat secara emosional, perilaku, dan kognitif. Selain itu juga terjadi interaksi antara guru-murid dan murid-murid. Selain itu, beberapa kendala yang dihadapi guru dalam menerapkan strategi negosiasi makna di kelas pragmatis adalah pemahaman siswa dalam memahami kosakata, idiom, dan makna. Artinya guru biasa menerjemahkan materi materi pragmatis bahasa Inggris ke dalam bahasa Indonesia. Selain itu, penulis menyarankan kepada peneliti selanjutnya untuk menyelidiki macam-macam keterlibatan siswa yang terjadi dalam proses pembelajaran bahasa Inggris.Kata kunci: Akuisisi Bahasa Kedua, negosiasi makna, interaksi kelas, keterlibatan siswa